2015
DOI: 10.2138/am-2015-4945
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of crystal structure of CaGeO3high-pressure perovskite phase and experimental determination of its Debye temperatures studied by low- and high-temperature single-crystal X-ray diffraction

Abstract: Single-crystal X-ray diffraction study of CaGeO 3 perovskite has been conducted over the temperature range of 98 to 1048 K. The crystal begins to deteriorate at a temperature above about 900 K and completely amorphizes by 980 K. The diffraction-intensity distribution and the structure refinements indicate that the Pbnm structure is kept until the occurrence of amorphization. The obtained unit-cell parameters, unit-cell volumes, bond lengths, and displacement parameters increase monotonously with increasing tem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 45 publications
3
13
0
Order By: Relevance
“…On the other hand, Figure 3 shows that the diffraction peaks begin to broaden at a temperature higher than 323 K and completely disappear by 448 K. This observation agrees well with the results of Andrault et al (1996), who reported that the SrGeO 3 perovskite, metastable at ambient pressure, amorphized near 500 K and that the amorphous phase began to recrystallize to the thermodynamically stable pseudowollastonite phase at a higher temperature. A similar observation was reported for the CaGeO 3 orthorhombic perovskite, which amorphizes near 923 K (Durben et al, 1991;Nakatsuka et al, 2015b).…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…On the other hand, Figure 3 shows that the diffraction peaks begin to broaden at a temperature higher than 323 K and completely disappear by 448 K. This observation agrees well with the results of Andrault et al (1996), who reported that the SrGeO 3 perovskite, metastable at ambient pressure, amorphized near 500 K and that the amorphous phase began to recrystallize to the thermodynamically stable pseudowollastonite phase at a higher temperature. A similar observation was reported for the CaGeO 3 orthorhombic perovskite, which amorphizes near 923 K (Durben et al, 1991;Nakatsuka et al, 2015b).…”
Section: Resultssupporting
confidence: 84%
“…Assuming a harmonic OPP, V OPP ðuÞ ¼ ðq=2Þhu 2 i d (Willis and Pryor, 1975), the OPP coefficient q, corresponding to the force constant, is related to the Debye temperature Θ D (Nakatsuka et al, 2015b):…”
Section: Temperature Dependence Of Mean-square Displacements (Msds) Omentioning
confidence: 99%
“…In particular, it is noteworthy that in both tetrahedral and octahedral coordination, the Ge-O bonds in SrGe 2 O 5 are still more covalent than the Si-O bonds in SrSi 2 O 5 . Such strong covalency of the Ge-O bonds in SrGe 2 O 5 affects atomic thermal vibrations, as was also discussed in SrGeO 3 cubic perovskite Nakatsuka et al, 2016) and CaGeO 3 orthorhombic perovskite (Nakatsuka, Kuribayashi et al, 2015). Indeed, the displacement ellipsoids of the O atoms largely elongate toward the direction of 'void space' in the structure, which is not filled with GeO 6 octahedra and GeO 4 tetrahedra, so that their thermal vibrations avoid interactions with adjacent Ge atoms (Fig.…”
Section: Effect Of Cation Size On the Crystal Structurementioning
confidence: 70%
“…Meanwhile, germanates have frequently been employed as model substances for the corresponding silicates (e.g. Nakatsuka et al, 2005Nakatsuka et al, , 2016Nakatsuka, Kuribayashi et al, 2015;Koganemaru et al, 2013) because they exhibit similar phase transformations to those of silicates at lower pressures. Phase and structural studies of germanates have thus provided important insights into phase transformations of silicate minerals in the Earth's interior.…”
Section: Introductionmentioning
confidence: 99%
“…In case of the germanate system, MgGeO 3 , MnGeO 3 and ZnGeO 3 form pPv upon heating to ~63 GPa (Hirose et al 2005), ~60 GPa (Tateno et al 2006) and ~115 GPa (Yusa et al 2014) respectively. Post-perovskite has not been observed in CaGeO 3 (Nakatsuka et al 2015) and…”
Section: 26mentioning
confidence: 95%